COMPARATIVE ANALYSIS OF BUDGET ACCOUNTING STANDARDS IN UZBEKISTAN AND INTERNATIONAL PUBLIC SECTOR ACCOUNTING STANDARDS - Makhamadalieva Makhliyokhon Makhamadmurod qizi (American Journals, 2025)
This study provides a comprehensive comparative analysis of Uzbekistan's Budget Accounting Standards and International Public Sector Accounting Standards (IPSAS). Through document analysis and comparative methodology, this research examines the key differences, similarities, and implementation challenges between these two accounting frameworks. The findings reveal significant gaps in asset recognition, revenue accounting, and financial reporting transparency that hinder Uzbekistan's alignment with international best practices. The study identifies critical areas requiring reform and provides recommendations for gradual convergence toward IPSAS adoption, contributing to the broader discourse on public sector accounting harmonization in emerging economies.
Keywords: Budget accounting, IPSAS, Uzbekistan, public sector accounting, financial reporting, convergence